Doxycycline increases prednisolone sensitivity in childhood acute lymphoblastic leukaemia - Styczyński, Jan (Contemporary Oncology/Współczesna Onkologia, 2009)
Glucocorticoids are the most important group of drugs in the therapy of childhood acute lymphoblastic leukaemia (ALL), and resistance of lymphoblasts to prednisolone both in vitro and in vivo is one of the most important adverse prognostic factors. We tested the hypothesis that the tetracycline antibiotic doxycycline (DCC), which inhibits protein synthesis and is known as having properties to upregulate expression of glucocorticoid receptor and having no anti-leukaemic activity, can modulate the response to prednisolone in childhood ALL. Samples of 60 childhood ALL and 12 children with normal marrow cells (NMC) were tested for sensitivity to prednisolone and doxycycline by the MTT assay and for cell cycle analysis by flow cytometry. DCC itself caused cell death in 15% of lymphoblasts, but not in NMC. When combined with prednisolone, DCC caused increase of its cytotoxicity in ALL median 2.17-fold, but not in NMC. In 13 cases of ALL samples, sensitization exceeded the value 1000, and in 14 cases, antagonism between these two compounds was observed. Sensitization was higher in relapsed patients, but no correlation was observed between ex vivo resistance of lymphoblasts to prednisolone and modulatory effect of DCC. In summary, we conclude that DCC might modulate prednisolone cytotoxicity in childhood ALL. This is possibly due to positive modulation of expression and function of glucocorticoid receptor; however, other mechanisms of cellular drug resistance might also contribute to this phenomenon.